Kedudukan Al-Qur’an dan Hadist sebagai Dasar Pendidikan Islam - Cahaya Putri Maharani; Fayola Nabila Putri; Muhammad Rendy Afriza; Irna Hasanah; Andriyani Andriyani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The Qur’an and Hadith are the main references for Islamic teachings and function as the essential basis for Islamic education. They function not only as a guide for the lives of Muslims but also as the basis for determining educational goals, values, curricula, and methods. The aim of Islamic education is to develop individuals who are balanced in faith, knowledge, morals, and skills, enabling them to fulfill their roles as servants of Allah and His representatives on earth. This research seeks to analyze the role of the Qur’an and Hadith as the fundamental basis of Islamic education and their influence on shaping educational objectives, values, curriculum design, and teaching methods. The research method used is a systematic review of national and international journal articles published from 2020 to 2025. The results show that Islamic education places emphasis on forming al-insan al-kamil individuals characterized by faith, knowledge, noble character, and a sense of responsibility. Through curricula and educational methods grounded in the Qur’an and Hadith, values such as faith, piety, honesty, and social concern are instilled.